A missense mutation in the seventh transmembrane domain constitutively activates the human Ca2+ receptor - Zhao, Xin-mei; Hauache, Omar; Goldsmith, Paul K.; Collins, Regina; Spiegel, Allen M. (FEBS letters, 1999)
A missense mutation, A843E, in the seventh transmembrane domain of the human Ca2+ receptor, identified in a subject with autosomal dominant hypocalcemia, was found to cause a constitutive activation while at the same time lowering the maximal response of the receptor to Ca2+. A truncated human Ca2+ receptor lacking the majority of the N‐terminal extracellular domain failed to respond to Ca2+ despite an excellent cell surface expression. The A843E mutant version of this truncated receptor showed constitutive activation. These results identify A843 as a critical residue for maintaining the inactive conformation of the human Ca2+ receptor. Substitution of glutamate, but not lysine or valine, for alanine 843 leads to activation of the human Ca2+ receptor in a manner that no longer depends upon Ca2+ binding to the extracellular domain.